Influence of the Heating Temperature and Fineness on the Hydration and Mechanical Property of Recycled Gypsum Plaster - Zhixin Li; Kaidong Xu; Jiahui Peng; Jina Wang; Jianwu Zhang; Qingxiao Li (Advances in Materials Science and Engineering)
Influence of the heating temperature and fineness on the hydration and mechanical property of recycled gypsum plaster was investigated to find the suitable heating temperature and fineness. According to the results, the setting time of recycled gypsum plaster increased with the increase of heating temperature, and the mechanical strength increased first and then decreased at a temperature of 165°C. Therefore, the suitable heating temperature was 165°C, and at this time, the initial setting time and final setting time were 8 min and 12.5 min, respectively, which met the requirements of the Chinese standard of GB/T 9776-2008. The strength of recycled gypsum plaster increased with the increase of specific surface area, and the low water to plaster ratio and high strength were achieved when the specific surface area was 1526 m2/kg. Therefore, it can be concluded that the suitable heating temperature was 165°C and the suitable specific surface area was 1526 m2/kg considering the properties and economics of recycled gypsum plaster.